Evolution of sun-shades outside building facades - Coetzee, Leon (Department of Computer Science, 2024)
The research objective behind this study is to compare ‘traditional' architectural sun-shades with evolved sun- shades to determine which best blocks direct sunlight from entering a window. Two geographical locations are tested along with two fa ̧cade conditions for each. The sun path on the summer solstice provides the projected sun rays, measured every fifteen seconds. The sun-shades are made up of points in 3D-space that form a ‘point cloud'. The points can be connected to form a surface and from there a geometric form. An Evolutionary Strategy, using self-adaptation, evolves the points within the point cloud to generate the sun- shade. Fitness for each point is determined by the number of sun rays the point can block from striking the win- dow surface; furthermore, the point may not obstruct the view from the window given certain conditions. The mean fitness for ten ‘traditional' architectural sun-shade solutions represented as point clouds, is compared to the mean fitness of the evolved sun-shade point cloud. This study provides two contributions to this field; firstly it provides a method to measure the fitness of ‘tra- ditional' sun-shades solutions and compares them with evolved solutions, secondly it provides a form for the so- lution. Architecturally, the form the evolved sun-shade takes becomes interesting. Finally, some possible improvements and modifications are further discussed.